2020
DOI: 10.1002/adhm.202001343
|View full text |Cite
|
Sign up to set email alerts
|

Microbubbles Containing Lysolipid Enhance Ultrasound‐Mediated Blood–Brain Barrier Breakdown In Vivo

Abstract: Ultrasound and microbubbles (MBs) offer a noninvasive method of temporarily enhancing blood–brain barrier (BBB) permeability to therapeutics. To reduce off‐target effects, it is desirable to minimize the ultrasound pressures required. It has been shown that a new formulation of MBs containing lysolipids (Lyso‐MBs) can increase the cellular uptake of a model drug in vitro. The aim of this study is to investigate whether Lyso‐MBs can also enhance BBB permeability in vivo. Female BALB/c mice are injected with eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Other studies have shown that microbubbles can be used for contrast-enhanced ultrasound imaging. [26][27][28] Ultrasound has already been widely used in microfluidics, for instance for isolating and sorting of microparticles, trapping and lysis of cells and for DNA fragmentation. [29][30][31][32] Huang's group has conducted research on acoustofluidics using trapped microbubbles or microstructure-enhanced ultrasound effects for different applications, such as microfluidic mixing, cell lysis and acoustofluidic pumping.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that microbubbles can be used for contrast-enhanced ultrasound imaging. [26][27][28] Ultrasound has already been widely used in microfluidics, for instance for isolating and sorting of microparticles, trapping and lysis of cells and for DNA fragmentation. [29][30][31][32] Huang's group has conducted research on acoustofluidics using trapped microbubbles or microstructure-enhanced ultrasound effects for different applications, such as microfluidic mixing, cell lysis and acoustofluidic pumping.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound exposure to the brain was carried out using a purpose-built setup (Figure 1 B) that allowed reproducible treatment of mice, whilst in an MRI cradle and in a stereotactic frame, and thus, enabling consistent positioning for comparative analysis, as described previously 40 . Briefly, animals were held in position in the cradle using cheek bars for the duration of ultrasound treatment so that the whole brain volume could be consistently exposed.…”
Section: Methodsmentioning
confidence: 99%
“…34 Various approaches to disrupt barrier integrity have been shown to improve movement of therapeutic agents across biological barriers. Such techniques include the use of microbubbles and ultrasound, 35 lasers, 36 microneedles, 37 and nanoparticles. 38…”
Section: Biological Barriers In Vivomentioning
confidence: 99%